EFFECT OF SPACING AND SODIUM NITRO PRUSSIDE ON GROWTH AND YIELD OF AFRICAN MARIGOLD DURING SUMMER IN ANDHRA PRADESH - D. APARNA, M. L. N. REDDY, A. V. D. DORAJEERAO, V. V. BHASKAR, P. SUBBARAMAMMA; K. UMA KRISHNA (The Journal of Research ANGRAU, 2022)
A two-year study from 2018 to 2019 conducted at Horticultural Research Station, Venkataramannagudem, Dr YSR Horticultural University, Andhra Pradesh, India on effect of spacing and sodium nitro prusside (SNP) concentration on plant growth and flower yield of African marigold cv. Bidhan Marigold-2 by inducing heat stress tolerance during summer revealed that closer spacing of 45 x 30 cm, higher SNP concentration of 200 μ M and their interaction effect recorded highest flower yieldha-1(165.959, 178.267, 209.953 respectively) and BCR (1.65, 1.95, 2.76 respectively) whereas for rest of the vegetative, flower and yield parameters,maximum values were recorded at wider spacing of 60 x 30 cm, higher SNP concentration of 200 μ M and interaction effect of 60 x 30 cm + 200 μ M SNP indicating heat stress tolerance during plant growth in summer.